CO2 Emission Suspection as Green House Gas Impact of Forest and Land Fire on Some Land Cover Type in Center Kalimantan, Year 2000-2009 - Bambang Hero Saharjo; Erianto Indra Putra; Umar Atik (Jurnal Silvikultur Tropika, 2012)
Land and forest fire can release carbon emissions into the air, for example happened in Central Kalimantan. Especially from land use conversion. Land and forest fire area can be predicted by using hotspot data. Carbon emissions measured by the potential of burnt area on every land covers. This research show that an increase in the number of hotspot from 2000 to 2009. The highest number of hotspot in 2006 reached 22,505 spot. The increasing number of hotspot form 2000 to 2009 is in line with the increasing of burned area on every land covers. Swamp shrub has the highest potential of burned area that reached 113,608.66 ha. Shrub converted to palm oil plantation released the highest carbon emission (801,764 ton). The highest carbondioxide emission on mineral land in Central Kalimantan was released from shrub in 2005 (459,427 ton). While on peat land, the highest carbondioxide emission was released from secondary swamp forest in 2005 (80,851 ton) and primary swamp forest in 2009 (180,531 ton).